Decoding glioblastoma survival: unraveling the prognostic potential of olfactory function in a prospective observational study - Christoph Oster; Aylin Matyar; Teresa Schmidt; Thomas Hummel; Elke Hattingen; Martha Jokisch; Daniel Jokisch; Jana Grieger; Giorgio Cappello; Kathrin Kizina; Lazaros Lazaridis; Yahya Ahmadipour; et al. (Neurological Research and Practice)
Abstract Introduction Olfactory impairment is common in glioblastoma and has been associated with unfavorable overall survival. However, prior studies were limited by imbalances in key prognostic factors and the absence of longitudinal olfactory assessments to evaluate treatment-related neurotoxicity. The aim of the study is to determine whether olfactory function serves as an independent prognostic marker for survival, neurocognitive outcomes, and quality of life in glioblastoma. Methods Prospective, multicenter cohort study enrolling 64 glioblastoma patients and 64 matched healthy controls. Patients are stratified by extent of resection, O6-Methylguanine-DNA Methyltransferase promoter methylation, radiographic involvement of olfactory regions, baseline olfactory status, age, and Karnofsky performance status. Olfactory function is assessed serially using Sniffin’ Sticks (identification and threshold tests) from diagnosis through treatment. Coronal T2- and T1-weighted MRI scans are reviewed independently by two blinded neuroradiologists to detect olfactory region involvement. Neurocognitive testing, psychosocial screening, and quality of life assessments are conducted at defined intervals. Next-generation sequencing from tumor tissue is employed to explore molecular underpinnings of hyposmia. Blood samples are collected in every study visit for potential parallel translational studies. Perspective This is the first longitudinal study evaluating olfactory function as a prognostic biomarker in glioblastoma. Findings may inform risk stratification, guide neuroprotective strategies, and improve survivorship care. Trial registration ClinicalTrials.gov, NCT06954636, date of registration 04-16-2025 (retrospectively registered); https://clinicaltrials.gov/study/NCT06954636?cond=glioblastoma&intr=olfactory&rank=1 .